The effect of chip thickness and extractive content on pulp yield, pulp quality and speed of soda AQ delignification - Burger, Roelof Arnoldus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1996.